Estimation of microclimate parameters on infestation rate of yellow stem borer (Scirpophaga incertulas) on MR297 rice variety - Idris, Dauda (2023)
Scirpophaga incertulas is a predominant insect pest in rice cultivation that causes significant yield losses and is responsible for severe infestation exhibiting dead heart and white ear symptoms at vegetative and reproductive stages. Rice is the second highestyielding grain and a staple diet in most countries. In Malaysia, rice is a vital plant, with an average daily consumption of 2.5 plates per head, and about 10% to 33% of the yield losses in the granary area of Malaysia during rice production are due to S. incertulas. However, information on the estimation of microclimate parameters in Malaysia on the infestation rate of yellow stem borer on MR297 rice variety is still not studied. The use of Artificial Neuron Network (ANN) and Multi-Linear Regression (MLR) in forecasting pest infestation and development has been used. However, this was not the case for yellow stem borer. Therefore, a series of experiments were conducted to obtain a study on the yellow stem borer. Adult yellow stem borers were collected using a Malaise trap from the Integrated Agricultural Development Area (IADA) Laut Barat Selangor. They released into a cage with 21-day-old paddy to allow them to copulate to achieve the following specific objective of the study. The first study objective was to investigate the in-vitro culture and developmental changes of S. incertulas under different microclimate conditions in the Laboratory (27.26ºC + 0.92 and RH of 67.43% + 1.3) and shade house (33.16ºC + 0.87 and RH 84.30% + 1.43). Based on the findings, culturing of S. incertulas under laboratory and shade house conditions assumes significance in addressing the developmental growth of S. incertulas via identifying the lengths and widths as essential parameters for appropriate identification of the larval and pupal stages. The development time taken by the S. incertulas increases as insects develop faster, leading to early population growth. The correlation analysis of the data showed a significant relationship between the length and width of the fourth and fifth instar development in the Laboratory correlated to the minimum and maximum relative humidity. In contrast, pupae length and width in the field were significantly related to the minimum relative humidity and maximum temperature. For the second aimed to determine the infestation and damage of S. incertulas on rice under different microclimatic conditions in Shade House (33.16ºC + 0.87 and RH of 84.30% + 1.43) and glass house (25.20ºC + 0.29 and RH of 74.50% + 2.12). The dead hearts at the vegetative phase revealed a significant mean percentage of infestation rate at 10 Days after treatments (DATS) to 40DATS ranging from 10.00% to 71.25% in the glass house, slightly higher than in the shade house 6.25% to 70.63%. Also, at the reproductive stage, the glass house had the highest infestation rate of white ears, which varied from 5.00% to 58.75%, in contrast to the shade house, which had a mean percentage of 5.00% to 31.88% during the 40DATS to 70DATS under different microclimate conditions. Therefore, microclimates like temperature and relative humidity significantly affect the infestation rate of the S. incertulas on rice. The final study aimed to estimate the yellow stem borer infestation rate with abiotic factor using an artificial neuron network (ANN) and Multi-linear regression model, which effectively estimate the best model and their comparison on performance. The Lavenberg-Marquardt algorithm was used to train the input and target. The slightly large dispensary between ANN's training, validation, and testing performance over MLR suggests that ANN revealed significant positive coefficients of determination between the microclimate and infestation rate of S. incertulas. The results showed a strong coefficient of determination between the S. incertulas infestation rate with the morning minimum and maximum temperature in a shade house compared to the glass house, where the infestation rate of S. incertulas was positively correlated to the afternoon minimum and maximum relative humidity. In conclusion, the estimation of microclimate parameters on the infestation rate of yellow stem borer on MR297 rice variety in Malaysia to estimate the infestation rate with abiotic factors was the first of its kind for modeling and forecasting the infestation rate of S. incertulas. The present study's finding recommends that rice farmers and entomologists develop a pest management program for yellow stem borer and stimulate research workers for sustainable bio-resource management. Further studies are required for proof of concept in the field experiment to ascertain the infestation rate of S. incertulas using forecasting of imaging processing and prediction with abiotic factors.